THE EFFECT OF USING SONG ON THE FOURTH-GRADE STUDENTS’ LEARNING MOTIVATION IN NATURAL SCIENCE LEARNING SUBJECT AT FREE METHODIST 2 PRIVATE ELEMENTARY SCHOOL MEDAN - Simbolon, Rosari Hotma J; Lumbanraja, Bogor; Silaban, Patri Janson; Abi, Antonius Remigius; Anzelina, Dewi (Jurnal pendidikan dan pengajaran, 2023)
This paper refers to research about the effect of using song as media on fourth-grade students' learning motivation in natural science learning subjects at Free Methodist 2 Private Elementary School Medan in the academic year 2022/2023. The research method used is the experimental method. The research population was 84 fourth-grade students from 3 classes at Free Methodist 2 Private Elementary School Medan in the academic year 2022/2023. The sampling technique used a purposive sample and the sample used was class IV C, which consisted of 30 students. The research results indicate that students' learning motivation using song media is categorized in the high category with an average score of 79.23 with a correlation test result of 0.865, which means rcount (0.865) ≥ rtable (0.361), hence Ha is accepted. Furthermore, there is a significant effect between the use of song media and students' learning motivation in natural science learning subjects in class IV of Free Methodist 2 Elementary School Medan. It can be seen from the results of the T-test research where tcount 9,123 ≥ ttable 1,071 that Ha is accepted. It shows that there is a positive and significant effect from the use of song media on the fourth-grade students' learning motivation in natural science learning subjects at SD Free Methodist 2 Medan in the academic year 2022/2023.